PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN, KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN DIMEDIASI OLEH KEPUASAN PELANGGAN (Studi Empiris Pada Rumah Makan Padang Surya Pamularsih Semarang) - Eko Teguh Winarko, 13.05.51.0073 (Students' Journal of Economic and Management, 2017)
This purpose of this study was to analysis the effect of of price perception, service quality and product quality to customer satisfaction and customer loyalty at Padang Surya Restaurant Semarang. The population in this study were customer who purchases the product more three times at Padang Surya Restaurant Semarang and the age more 17 years old. The number of samples studied was as many as 110 people were selected as respondents by using purposive sampling technique. Data collection methods used in this study is a questionnaire filled by respondents. The analysis used in this research is linear regression analysis to examine the effect of partially each independent variable that is price perception, service quality and product quality to dependent variable that is customer satisfaction and customer loyalty. And use path analysis. The results of this study indicate that the perception of price, quality of service, and product quality have a positive and significant impact on customer satisfaction in Padang Surya Restaurant Semarang. Price perception, service quality, and product quality have positive and significant influence to customer loyalty at Padang Surya Restaurant Semarang. Customer satisfaction variables do not mediate the variable of price perception, service quality and product quality to customer loyalty. Keywords: Price Perception, Service Quality, Product Quality, Customer Satisfaction and Customer Loyalty.